A Review of the Environmental Impact of Buildings with an Emphasis on Performance Assessment Tools and Their Incorporation of LCA - Vidhyalakshmi Chandrasekaran; Jolanta Dvarionienė (Advances in Civil Engineering)
Background. The environmental performance of buildings has been a focus of interest over the years in the building sector. Numerous building environmental assessment tools (BEA) have evolved to follow the lead of sustainability by updating categories and criteria from a lifecycle perspective. Therefore, it is timely to review the existing methods that already integrated LCA in their processes. The purpose of this study unfolds in three ways: (1) to review the existing BEA methods and LCA studies in residential buildings, (2) to compare the most adopted BEA methods, and (3) to study the integration of LCA and sustainability aspects applied within each selected BEA method. Methods. Scopus and Web of Science databases were searched for articles published between August 2010 and August 2021 in English. To identify studies and to conduct this review, four keywords, namely “Building Assessment Tools,” “Residential Building,” “LCA,” and “Sustainability” (and their derivatives), were used. The articles were searched so that all four keywords or at least a derivative of each keyword would appear. Furthermore, the outcomes of the database search were categorized as LCA and BEA for the review. Moreover, the seven most adopted rating systems were selected for review and comparison based on (1) the scope of buildings assessed, (2) lifecycle phases assessed, (3) assessment criteria, and (4) the user of tools. Findings. Of the 42 articles that met the enclosure criteria, 20 articles covered the environmental impact and 22 articles covered LCA. The review reveals that most of the analyzed systems focus more on the operational stage than on the other stages. Each BEA method is diverse in terms of its users, criteria, and regions and creates a niche among assessment methods. Conclusions. The main conclusion of this study is that a great deal of work is required to achieve the goal of making the existing “environmental” building assessment tools more sustainable. At the same time, a focus on the better implementation of LCA functionalities at each stage and a complement by integrating socioeconomic-based LCA models were also required.